2020
DOI: 10.1111/hel.12753
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal microbiome in patients with or without Helicobacter pylori infection

Abstract: Background Intestinal microbiota are recognized as an organ with important physiological functions whose alterations have been associated with common diseases including inflammatory intestinal conditions, malnutrition, type‐2 diabetes, and cardiovascular diseases. The composition and function of the microbiota in the distal part of the intestine has been mainly described, while there is limited information on the small intestine microbiota. The objective of the present study was to describe the duodenal microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…In the present study, Proteobacteria and Firmicutes were the two major phyla in the mucosa of the descending duodenum in both groups. Compared with duodenal luminal microbiota where Firmicutes and Bacteroidetes are the two major phyla 22 , 23 , the findings from the current study were consistent with previous studies that Proteobacteria and Firmicutes are major phyla in the duodenal mucosa 17 , 24 . However, some previous studies on duodenal mucosa-associated microbiota have reported Firmicutes to be the phylum with the highest relative abundance 25 , 27 , which is inconsistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, Proteobacteria and Firmicutes were the two major phyla in the mucosa of the descending duodenum in both groups. Compared with duodenal luminal microbiota where Firmicutes and Bacteroidetes are the two major phyla 22 , 23 , the findings from the current study were consistent with previous studies that Proteobacteria and Firmicutes are major phyla in the duodenal mucosa 17 , 24 . However, some previous studies on duodenal mucosa-associated microbiota have reported Firmicutes to be the phylum with the highest relative abundance 25 , 27 , which is inconsistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies on duodenal microbiota have sampled various sites within the portions of the duodenum. In addition, some studies sampled duodenal aspirates to investigate luminal microbiota 22 , 23 , while others sampled mucosal tissue to investigate mucosa-associated microbiota 17 , 24 , 25 . Recently, Constante et al 26 reported that gut location is a key determinant of duodenal microbiota composition and predicted function in celiac disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not have access to the information about H. pylori presence in the patients and it was shown in the previous research that it might influence the microbiota composition with the increase of alpha and beta-diversity. On the other hand, the pattern of microbiota composition did not differ significantly in the infected patients [ 30 ]. Furthermore, eradication therapy may also influence the microbiota composition with the increase of Proteobacteria .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, gut microbiota plays an important role in the development of atherosclerosis, and there is a relationship between gastric and intestinal microbiome and H. pylori infection. It has been demonstrated that there are significant differences in the diversity and number of gut microbiota between H. pylori infected and uninfected individuals ( 38 , 39 ). It will be important to determine if CagA + H. pylori infection could impair the population and balance of gut microbiota more than CagA – H. pylori infection, thus leading to endothelial dysfunction and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%